(FeO)2FeBO3 nanoparticles attached on interconnected nitrogen-doped carbon nanosheets serving as sulfur hosts for lithium–sulfur batteries - Wang, Junhai; Huang, Huaqiu; Chen, Chen; Zheng, Jiandong; Cao, Yaxian; Joo, Sang Woo; Huang, Jiarui (Frontiers of materials science, 2024)
There are still many challenges including low conductivity of cathodes, shuttle effect of polysulfides, and significant volume change of sulfur during cycling to be solved before practical applications of lithium–sulfur (Li–S) batteries. In this work, (FeO) 2 FeBO 3 nanoparticles (NPs) anchored on interconnected nitrogen-doped carbon nanosheets (NCNs) were synthesized, serving as sulfur carriers for Li–S batteries to solve such issues. NCNs have the cross-linked network structure, which possess good electrical conductivity, large specific surface area, and abundant micropores and mesopores, enabling the cathode to be well infiltrated and permeated by the electrolyte, ensuring the rapid electron/ion transfer, and alleviating the volume expansion during the electrochemical reaction. In addition, polar (FeO) 2 FeBO 3 can enhance the adsorption of polysulfides, effectively alleviating the polysulfide shuttle effect. Under a current density of 1.0 A·g −1 , the initial discharging and charging specific capacities of the (FeO) 2 FeBO 3 @NCNs-2/S electrode were obtained to be 1113.2 and 1098.3 mA·h·g −1 , respectively. After 1000 cycles, its capacity maintained at 436.8 mA·h·g −1 , displaying a decay rate of 0.08% per cycle. Therefore, combining NCNs with (FeO) 2 FeBO 3 NPs is conducive to the performance improvement of Li–S batteries.